2019
DOI: 10.1071/wr18122
|View full text |Cite
|
Sign up to set email alerts
|

Estimating kangaroo density by aerial survey: a comparison of thermal cameras with human observers

Abstract: ContextAerial surveys provide valuable information about the population status and distribution of many native and pest vertebrate species. They are vital for evidence-based monitoring, budget planning and setting management targets. Despite aircraft running costs, they remain one of the most cost-effective ways to capture distribution and abundance data over a broad area. In Australia, annual surveys of large macropods are undertaken in several states to inform management, and in some jurisdictions, to help s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…A possible reason for the non-detection of small terrestrial and arboreal mammals in open habitats compared to dense vegetation by thermal imaging is the combined effect of surface reflection from sunlight and thermal radiation from the canopy and ground. Compared to studies by [14], our study shows the same findings, washed-out thermal images in open areas due to high surface reflectance, making it challenging to distinguish animals from their background. The canopy of trees in the surrounding is a significant barrier for thermal sensors to detect animals.…”
Section: Animal Visibilitysupporting
confidence: 64%
“…A possible reason for the non-detection of small terrestrial and arboreal mammals in open habitats compared to dense vegetation by thermal imaging is the combined effect of surface reflection from sunlight and thermal radiation from the canopy and ground. Compared to studies by [14], our study shows the same findings, washed-out thermal images in open areas due to high surface reflectance, making it challenging to distinguish animals from their background. The canopy of trees in the surrounding is a significant barrier for thermal sensors to detect animals.…”
Section: Animal Visibilitysupporting
confidence: 64%
“…It is now possible to test RSO performance with parallel digital camera systems that are inclined at the same angle as RSO-viewing, and image the same strip. Recent cross-comparisons in simultaneous RSO and OCC counting have been conducted for narwhal in Greenland (Monodon monoceros) (Br€ oker et al 2019) and kangaroos in Australia (Lethbridge et al 2019) where thermal image-based estimates of kangaroo density were 30% higher than RSO estimates. In Kenya, an RSObased SRF was run concurrently with high-resolution camera systems in a multi-species count over a large protected area, and it was found that RSOs missed, for example, 60% of giraffe and 66% of the large antelopes (Lamprey et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…drones) are capable of moving fast, scanning forests from top to bottom and are very promising for expanding the scale of canopy surveys that are very useful in studying wildlife ecology. Drone imagery has proven useful for wildlife surveys in open areas, for example, guanaco [1], Artic birds [2], kangaroo [3], caribou [4], waterfowl [5], hippos [6], and crocodile [7]. Meanwhile, for animals living in tree canopies, UAVs are not widely used because of the difficulty of visually detecting these animals with standard aerial imagery.…”
Section: Introductionmentioning
confidence: 99%